2012
DOI: 10.2337/db11-0884
|View full text |Cite
|
Sign up to set email alerts
|

GLUT4 and Glycogen Synthase Are Key Players in Bed Rest–Induced Insulin Resistance

Abstract: To elucidate the molecular mechanisms behind physical inactivity–induced insulin resistance in skeletal muscle, 12 young, healthy male subjects completed 7 days of bed rest with vastus lateralis muscle biopsies obtained before and after. In six of the subjects, muscle biopsies were taken from both legs before and after a 3-h hyperinsulinemic euglycemic clamp performed 3 h after a 45-min, one-legged exercise. Blood samples were obtained from one femoral artery and both femoral veins before and during the clamp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 49 publications
6
99
0
1
Order By: Relevance
“…Additionally, the blood stagnation inside the jugular vein may contribute to increased intracranial pressure (Besnard et al 2002;Zhang and Hargens 2014), potentially resulting in impaired cerebrovascular reactivity (Zuj et al 2012). Several studies have reported an increase in circulating insulin in astronauts during spaceflight (Macho et al 2003;Hughson et al unpublished data, personal communication 2015) and an increase in glycemia and insulin resistance during bed rest (Cree et al 2010, Biensø et al 2012. These changes may be in part due to altered abdominal organ function from splanchnic venous pooling.…”
Section: Tibv (Cm 2 )mentioning
confidence: 91%
“…Additionally, the blood stagnation inside the jugular vein may contribute to increased intracranial pressure (Besnard et al 2002;Zhang and Hargens 2014), potentially resulting in impaired cerebrovascular reactivity (Zuj et al 2012). Several studies have reported an increase in circulating insulin in astronauts during spaceflight (Macho et al 2003;Hughson et al unpublished data, personal communication 2015) and an increase in glycemia and insulin resistance during bed rest (Cree et al 2010, Biensø et al 2012. These changes may be in part due to altered abdominal organ function from splanchnic venous pooling.…”
Section: Tibv (Cm 2 )mentioning
confidence: 91%
“…In line with previous studies of insulinresistant conditions including individuals with obesity, PCOS and type 2 diabetes [4-6, 25, 29], we did, however, observe a lack of insulin-induced dephosphorylation of GS at sites 2+2a in both type 2 diabetes and obesity. These phosphosites have previously been found to be responsive to insulin stimulation in a number of healthy lean participant populations [4,25,43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mechanisms through which severe spasticity ameliorates the derangement of body compositions and glucose homeostasis could be investigated. For example, differences in the expression of glucose transport protein, GLUT4 proteins, 30 IGF-1 concentration 7,29 and muscle fiber type composition 22,23 have been suggested as related mechanisms.…”
Section: Discussionmentioning
confidence: 99%